Report of Meeting. The Twenty-third Katowice-Debrecen Winter Seminar on Functional Equations and Inequalities Brenna (Poland), January 31 - February 3, 2024 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2024)
Report of Meeting. The Twenty-third Katowice-Debrecen Winter Seminar on Functional Equations and Inequalities Brenna (Poland), January 31 - February 3, 2024.